Melville, shame, and the evil eye : a psychoanalytic reading - Adamson, Joseph, 1950- (Albany, NY : State University of New York Press, 1997)
This study offers a complex analysis of the psychodynamic role of shame in Melville's work, with detailed readings of Moby-Dick, Pierre, and "Billy Budd." Its concrete application of the rich analytic framework supplied by work of such theorists as Heinz Kohut, Leon Wurmser, Silvan Tomkins, and Donald Nathanson implicitly challenges the contemporary reliance on an often abstract poststructuralist model of psychoanalysis.
Melville and shame -- pt. 1. Shame and attachment : How to make a misanthrope ; Mortifying inter-indebtedness ; The inexorable self -- pt. 2. Shame, resentment, and envy : Motiveless malignity ; Turning the tables -- pt. 3. The evil eye : Dangerous mergers ; The evil eye -- "That truth should be silent I had almost forgot."
Includes bibliographical references (pages 309-335) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Melville, Herman, -- 1819-1891 -- Knowledge -- Psychology; Melville, Herman, -- 1819-1891 -- Psychology; Melville, Herman, -- 1819-1891; Psychoanalysis and literature -- United States -- History -- 19th century; Psychological fiction, American -- History and criticism; Novelists, American -- 19th century -- Psychology; Evil eye in literature; Shame in literature; Psychanalyse et littérature -- États-Unis -- Histoire -- 19e siècle.; Romanciers américains -- 19e siècle -- Psychologie; Mauvais œil dans la littérature.; Honte dans la littérature.; LITERARY CRITICISM -- American -- General; Evil eye in literature; Novelists, American -- Psychology; Psychoanalysis and literature; Psychological fiction, American; Psychology; Shame in literature; United States; American Literature; English; Languages & Literatures; 1800-1899; Criticism, interpretation, etc; History